Indicadores de estresse, ansiedade e depressão de mães de bebês com risco ao desenvolvimento - Alves, Gilda Maria Albaricci Nex [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study aimed to describe the parental stress indicators, anxiety and depression in mothers of babies and relating them to maternal variables (age, marital status, education and adherence to the program) and to the baby (gender, age, birth order, unit of use and severity of the condition) and also identify and correlate clinical indicators for stress, anxiety and depression of mothers of babes at risks to development, before and after their participation in a Family Support Program, part of a Essentials stimulation program. The instruments Parental Stress Index (PSI-4 Short Form), State - Trait Anxiety Inventory-State (STATI) and Baptista Depression Scale - EBADEP-A were applied. The study was performed in two stages. At first, we analyzed a sample of 53, mothers during the search for stimulation service to the child. The second stage they attended 36 mothers who remained in the institution with their babies and participated in the Family Suport Group. The data relating to the first phase indicated that most of the sample of babies look for the service at less than six months. Among mothers, those with stable union and high shool or completed college are most frequent. The results in the pre-assessment showed stress on Parental Distress in 26% of participants. On the IDATE, 40% of mothers had Trait Anxiety, most of participants reported no depression. Comparing the emotional health of mothers of babies at severe risk to the development and mothers of babies at moderate risk, it was observed medium result being higher among mothers of babies at severe risk to the development in the three instruments used, but there was significant difference only in relation to Trait Anxiety Analyzing accession or not to the program, it was observed that 69% have children with severe gravity condition and considering their emotional indicators they had higher average regarding to the parental stress indicators; more mothers showed clinical level of...

O presente estudo teve por objetivo descrever os indicadores de estresse parental, ansiedade e depressão das mães de bebês e relacioná-los com variáveis maternas (idade, estado civil, escolaridade e adesão ao programa) e do bebê (sexo, idade, ordem de nascimento, uso de aparelho e gravidade da condição) e também, identificar e correlacionar indicadores clínicos para estresse, ansiedade e depressão de mães de bebês com riscos ao desenvolvimento, antes e depois da sua participação em um Programa de Apoio às Famílias, parte de um Programa de Estimulação Essencial. Foram aplicados os instrumentos Índice de Stress Parental (PSI-4 Short Form), Inventário de Ansiedade Traço-Estado (IDATE) e Escala Baptista de Depressão - EBADEP - A. O estudo foi desenvolvido em duas etapas. Na primeira, analisou-se uma amostra de 53 mães por ocasião da procura pelo serviço de estimulação para o filho. Na segunda fase participaram 36 mães que permaneceram na instituição com seus bebês e participaram do Grupo de Apoio à Família. Os dados relativos à primeira fase apontaram que a maioria dos bebês da amostra chega para o serviço com menos de seis meses. Entre as mães são mais frequentes aquelas com união estável e com ensino médio ou superior completo. Os resultados na pré-avaliação apontaram estresse em Angústia Parental em 26% das participantes. No IDATE, 40% das mães apresentaram Ansiedade Traço; a maioria das participantes relatou ausência de depressão. Comparando a saúde emocional de mães com bebês com risco severo ao desenvolvimento e mães de bebês com risco moderado observou-se resultado médio maior entre as mães de bebês com risco severo para o desenvolvimento, nos três instrumentos utilizados, porém observou-se diferenças significantes somente em relação à Ansiedade Traço. Analisando a adesão ou não ao programa, observou-se que 69% tem filhos com quadro de gravidade severo e considerando os seus...
Indicators of stress, anxiety and depression of mothers of babies at risk to development
Keywords: Maternidade; Stress (Psicologia); Ansiedade; Crianças - Desvio do desenvolvimento; Maternity